Procalcitonin in the Early Course Post Pediatric Cardiac Surgery. Issue 7 (July 2016) - Zant, Robert; Stocker, Christian; Schlapbach, Luregn Jan; Mayfield, Sara; Karl, Tom; Schibler, Andreas
Abstract : Objective: Procalcitonin has emerged as a promising infection marker, but previous reports from small-sized studies suggest nonspecific elevation of procalcitonin after pediatric heart surgery. As procalcitonin is increasingly used as a marker for infection in the PICU, the aim of this study was to identify factors associated with postoperative procalcitonin elevation and to investigate the role of procalcitonin as an early marker of outcome after cardiac surgery. Design: Prospective observational study. Setting: Single, tertiary referral PICU. Patients: Patients aged 0–16 years following cardiac surgery with or without cardiopulmonary bypass. Interventions: Procalcitonin was measured in all patients at admission to PICU, and on postoperative day 1 and 2. Outcome variables included major adverse event, length of stay in PICU, postoperative renal failure requiring temporary dialysis, duration of mechanical ventilation and duration of inotropic support. A major adverse event was defined as cardiac arrest, need for postoperative extracorporeal life support or death within 3 months of cardiac surgery. Measurements and Main Results: In 221 included patients who underwent 232 operations, procalcitonin at admission to PICU was significantly associated with mechanical ventilation prior to surgery ( p = 0.001), preoperative myocardial dysfunction ( p = 0.002), duration of cardiopulmonary bypass ( p < 0.001), intraoperative cross-clamp time ( p = 0.015), and serum lactate at admission ( p < 0.001). Patients suffering a major adverse event and patients with postoperative renal failure had significantly higher procalcitonin levels at admission to PICU ( p = 0.04 and 0.01, respectively). Furthermore, procalcitonin levels at admission correlated significantly with the length of stay in the PICU ( p = 0.005), time on mechanical ventilation ( p = 0.03), and duration of inotropic support ( p = 0.02). Conclusions: Elevated levels of procalcitonin in the early phase after pediatric cardiac surgery are a marker for increased risk for major adverse events and postoperative renal failure and increased postoperative morbidity.